Adenomyosis and endometrial cancer: determining its role as a biological contributor or incidental coexistence - Vinita Shiwali; Ying Tang; Miaoyu Xue; Rebecca Yemeli Djouda; Xintong Cai; Zheng Peng; Jingru Zhang; Liping Han (BMC Cancer)
Abstract Background Numerous studies have explored the histological overlap between endometrial carcinoma and adenomyosis, yet the clinical implications of their co-occurrence remain ambiguous. This study aims to evaluate the impact of adenomyosis on the staging, progression, and prognosis of endometrial cancer. Method This retrospective cohort study analyzed 388 endometrial cancer (EC) patients undergone hysterectomy with lymphadenectomy between January 2019 to Decmber 2024 after ethical approval (No.: 2024-KY-0671–001). The diagnostic criterion for adenomyosis was the identification of endometrial glands and stroma infiltrating the myometrium at a depth of ≥ 2.5 mm from the endometrial-myometrial junction. Variables included demographics, surgery type, histopathology, stage, molecular markers, treatment, and survival. Kaplan–Meier and log-rank tests assessed survival. Statistical analysis used Mann–Whitney U and Chi-square tests (P < 0.05). Multivariate Cox regression was unfeasible due to limited recurrence events and disease-free survival outcomes are provided as supplementary material. Results Among 388 EC patients, 73 (18.8%) had adenomyosis and 315 (81.2%) did not. The adenomyosis group was younger (median age 52 vs. 55 years, P = 0.011) and had a lower menopause rate (63% vs. 75.2%, P = 0.049). Adjuvant therapy was less frequent in the adenomyosis group (21.9% vs. 37.8%, P = 0.015), while concurrent endometrial hyperplasia was more common (64.4% vs. 32.4%, P < 0.001). No significant differences were observed in tumor characteristics, complications, TCGA subtypes, or survival outcomes. Median follow-up was 56 months for the adenomyosis group and 61 months for the non-adenomyosis group. Conclusion This study shows that adenomyosis does not affect tumor progression or survival outcomes, indicating a neutral role in endometrial cancer prognosis. However, the interpretation of survival statistics is limited by the low recurrence rate. Patients with adenomyosis are younger, have a lower menopause rate, and require less adjuvant therapy. The higher prevalence of endometrial hyperplasia suggests a potential link to tumor pathogenesis. Overall, adenomyosis appears to be an incidental co-occurrence rather than a biological contributor to endometrial cancer.